2021
DOI: 10.1186/s12951-021-00907-3
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared light fluorescence imaging-guided biomimetic nanoparticles of extracellular vesicles deliver indocyanine green and paclitaxel for hyperthermia combined with chemotherapy against glioma

Abstract: Background We investigated the therapeutic effect of targeting extracellular vesicles (EVs) loaded with indocyanine green (ICG) and paclitaxel (PTX) on glioma. Methods Raw264.7 cells were harvested to extract EVs for the preparation of ICG/PTX@RGE-EV by electroporation and click chemistry. We evaluated the success of modifying Neuropilin-1 targeting peptide (RGE) on the EV membrane of ICG/PTX@RGE-EV using super-resolution fluorescence microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Fundamentally, the metaanalysis results were based on unadjusted estimates because some studies did not provide detailed information to calculate the adjusted estimates. Definitely, chemotherapy and other therapeutic interventions can also alter the EV profile (Ab Razak et al, 2019;Wang et al, 2021), which has been out of control in reported studies. In this regard, further research should validate the diagnostic value of EV indices in cancer patients who receive different treatments, such as chemotherapy, immunotherapy, or radiotherapy, and differentiate between those treated with chemo radiation and those treated with monotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Fundamentally, the metaanalysis results were based on unadjusted estimates because some studies did not provide detailed information to calculate the adjusted estimates. Definitely, chemotherapy and other therapeutic interventions can also alter the EV profile (Ab Razak et al, 2019;Wang et al, 2021), which has been out of control in reported studies. In this regard, further research should validate the diagnostic value of EV indices in cancer patients who receive different treatments, such as chemotherapy, immunotherapy, or radiotherapy, and differentiate between those treated with chemo radiation and those treated with monotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…ICG/PTX@RGE-EV shows good photothermal properties and promotion of PTX release from EVs, when stimulated by 808-nm laser light. Then, they target U251 cells, with activation of the Caspase-3 pathway and elevated apoptosis, which increases the median survival of glioma mice (Wang et al., 2021 ). What’s more, the significantly reduced tumor volume was observed in mice following targeting combined therapy (ICG/PTX@RGE-EV + NIR) compared with mice treated with chemotherapy, (PTX@RGE-EV), hyperthermia (ICG@RGEEV + NIR), or non-targeted chemotherapy-hyperthermia (ICG/PTX@EV + NIR).…”
Section: Drug Combination Strategy Based On Multifunctional Nano Drug...mentioning
confidence: 99%
“…ICG/PTX@RGE-EV shows good photothermal properties and drug release ability. Furthermore, this DDS can target U251 cells completely, activate the Caspase-3 pathway through chemotherapy and hyperthermia, and enhance U251 cell apoptosis 161 ( Figure 5 C ).…”
Section: Construction Of Tumor-derived Extracellular Vesicles As Drug...mentioning
confidence: 99%
“…C) ICG/PTX@RGE-EV can effectively target glioma to enact the Caspase-3 pathway through chemotherapy-hyperthermia in commitment to glioma cell apoptosis, which implies cancer development is smothered. Adapted with permission from 161 . Copyright Year 2021, Springer Nature.…”
Section: Figurementioning
confidence: 99%